2012
DOI: 10.1515/cclm-2012-0649
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of CCLM to advances in quality control

Abstract: The discipline of laboratory medicine is relati vely young when considered in the context of the history of medicine itself. The history of quality control, within the context of laboratory medicine, also enjoys a relati vely brief, but rich history. Laboratory quality control continues to evolve along with advances in automation, measure ment techniques and information technology. Clinical Chemistry and Laboratory Medicine (CCLM) has played a key role in helping disseminate information about the proper use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In US clinical laboratories, quality control practices are hugely divergent in addition to being costly (2 ). In a recent review, Kazmierczak stated, "the costs associated with performing quality control testing and the costs associated with evaluating, reviewing and maintaining quality control records are not trivial" (3 ). He cited a developing nation hospital study that found the costs of quality to be 22% of total direct laboratory expenses, with 89% of the costs for maintaining quality associated with calibration and analysis of quality control material necessary to confirm the accuracy and reliability of test results (4 ).…”
mentioning
confidence: 99%
“…In US clinical laboratories, quality control practices are hugely divergent in addition to being costly (2 ). In a recent review, Kazmierczak stated, "the costs associated with performing quality control testing and the costs associated with evaluating, reviewing and maintaining quality control records are not trivial" (3 ). He cited a developing nation hospital study that found the costs of quality to be 22% of total direct laboratory expenses, with 89% of the costs for maintaining quality associated with calibration and analysis of quality control material necessary to confirm the accuracy and reliability of test results (4 ).…”
mentioning
confidence: 99%